"Illegitimate" Bodies in Legitimate Times: Life, Liberty, and the Pursuit of Movement: National Association for Kinesiology in Higher Education 26th Delphine Hanna Commemorative Lecture 2017. Issue 2 (3rd April 2017) - Culp, Brian
ABSTRACT: Drawing on Michel Foucault's concepts of state racism and biopower, the author of the 26th Delphine Hanna Lecture presents several claims: (a) that the idea of the illegitimate outsider in Western world governments like the United States has largely been influenced by ancient Greek ideals, (b) that a host of policies and intentional actions by power brokers create derision and hierarchies between "old" and "new" immigrant groups, and (c) neoliberal ideology couched in actions that aim "to protect the state" is nothing more than a recoding of traditional racist rhetoric that expands systemic racism. The author identifies the capabilities approach, asset based community development, and framing movement and physical activity as issues of justice as critical strategies to ensure equal rights for all.